Erectile dysfunction and later cardiovascular disease in men with type 2 diabetes: Prospective cohort study based on the ADVANCE (Action in Diabetes and Vascular Disease: Preterax and Diamicron Modified-Release Controlled Evaluation) trial - Batty, G.; Li, Q.; Czernichow, S.; Neal, B.; Zoungas, S.; Huxley, Rachel; Patel, A.; De Galan, B.; Woodward, M.; Hamet, P.; Harrap, S.; Poulter, N.; et al. (2010)
Objectives The aim of this study was to examine the relationship between erectile problems in men and cardiovascular disease (CVD) mortality. Background Although there are plausible mechanisms linking erectile dysfunction (ED) with coronary heart disease (CHD) and stroke, studies are scarce. Methods In a cohort analysis of the ADVANCE (Action in Diabetes and Vascular Disease: Preterax and Diamicron Modified-Release Controlled Evaluation) trial population, 6,304 men age 55 to 88 years with type 2 diabetes participated in a baseline medical examination when inquiries were made about ED. Over 5 years of follow-up, during which study members attended repeat clinical examinations, the presence of fatal and nonfatal CVD outcomes, cognitive decline, and dementia was ascertained. Results After adjusting for a range of covariates, including existing illness, psychological health, and classic CVD risk factors, relative to those who were free of the condition, baseline ED was associated with an elevated risk of all CVD events (hazard ratio: 1.19; 95% confidence interval: 1.08 to 1.32), CHD (hazard ratio: 1.35; 95% confidence interval: 1.16 to 1.56), and cerebrovascular disease (hazard ratio: 1.36; 95% confidence interval: 1.11 to 1.67). Men who experienced ED at baseline and at 2-year follow-up had the highest risk for these outcomes. Conclusions In this cohort of men with type 2 diabetes, ED was associated with a range of CVD events. © 2010 American College of Cardiology Foundation.